Adapting Free, Prior, and Informed Consent (FPIC) to Local Contexts in REDD+: Lessons from Three Experiments in Vietnam - Pham Thu Thuy; Castella, J.C.; Lestrelin, Guillaume; Mertz, O.; Le, D.N.; Moeliono, M.; Nguyen Quang Tan; Vu, T.H.; Nguyen, D.T. (MDPI, 2015)
Free, prior, and informed consent (FPIC) is a means of ensuring that people’s rights are respected when reducing emissions from deforestation and forest degradation, and enhancing forest carbon stocks (REDD+) projects are established in developing countries. This paper examines how FPIC has been applied in three projects in Vietnam and highlights two key lessons learnt. First, as human rights and democracy are seen as politically sensitive issues in Vietnam, FPIC is likely to be more accepted by the government if it is built upon the national legal framework on citizen rights. Applying FPIC in this context can ensure that both government and citizen’s interests are achieved within the permitted political space. Second, FPIC activities should be seen as a learning process and designed based on local needs and preferences, with accountability of facilitators, two-way and multiple communication strategies, flexibility, and collective action in mind.